Irrigação com águas salinas e adubação organomineral no cultivo do amendoim - Silva, Elane Bezerra da (2020)
The use of organic sources such as biofertilizers and vegetable ash associated with mineral fertilizers can be an alternative to mitigate salt stress in agricultural crops. In this sense, the objective of this work was to evaluate the effects of the interaction between irrigation with saline water and different forms of organomineral fertilization on growth, leaf contents, gas exchange and productivity of peanut plants. The experiment was carried out in a greenhouse located at the Universidade da Integração da Lusofonia Afro-Brasileira, in Redenção-CE, in a completely randomized design, in a 5 x 2 factorial scheme, referring to five forms of fertilization (F1 = 100% mineral; F2 = 100% bovine biofertilizer; F3 = 100% vegetal ash; F4 = 50% mineral + 50% bovine biofertilizer and F5 = 50% mineral + 50% vegetal ash) and two levels of electrical conductivity of irrigation water (1,0 and 5,0 dS m-1), with 4 repetitions. Growth variables were analyzed: plant height, stem diameter and number of leaves; gas exchange variables: stomatal conductance, CO2 concentration, chlorophyll index, transpiration, photosynthesis, leaf temperature and efficient use of water; the leaf contents of N, P, K, Ca, Mg and Na; and productivity variables: number, length, diameter and mass of pods and productivity. Saline stress, under all fertilizations, affected plant height, number of leaves and stem diameter. Plants irrigated with low salinity water had the highest values of stomatal conductance, photosynthesis and transpiration. The water with a higher concentration of salts increased the leaf temperature of the plants and when associated with F2 fertilization it caused a higher relative chlorophyll content and efficiency in the use of water. The F1, F2 and F3 fertilizations attenuated the salt stress and increased the N and Ca content in the leaves. The high salinity irrigation water associated with F2 fertilization caused an increase in the P content in the plants. The same water caused a reduction in the K content in fertilizations F2 and F3 and a reduction in the Mg content in fertilizations F2 and F4. High salinity water increased the Na content in all forms of fertilization, except in F3. Fertilization with bovine biofertilizer was the most efficient to mitigate the salt stress on the peanut productivity variables.